2020
DOI: 10.3892/mmr.2020.10966
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the hypoxia inducible factor 1/hypoxic response element pathway in rat myocardial ischemia/diazoxide post‑conditioning

Abstract: ischemic post-conditioning (iPo) and diazoxide post-conditioning (dPo) has been proven to reduce myocardial ischemia reperfusion injury (Miri); however, the mechanisms of iPo/dPo are still not clear. The present study aimed to investigate whether mitochondrial aTP-sensitive potassium channels (mitoK aTP) channels are activated by iPo/dPo, which may further activate the hypoxia inducible factor 1/hypoxic response element (HiF-1/Hre) pathway to mitigate Miri. using a langendorff perfusion device, healthy male (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Fortunately, numerous animal studies evaluating diverse protective mechanisms have confirmed the efficacy of cardioprotection in ameliorating MIRI. [1][2][3][4][5][6] The actual clinical application of some of these strategies, however, does not match the animal study applications, and it is difficult to predict the consequences in clinical practice from those seen in experimental research. [7][8][9] In this context, the unclear mechanism underlying the development of apoptotic pathways or involving key molecules in MIRI might significantly matter, especially for cell death and even associated signalling pathways during ischaemia-reperfusion, such as ERS-related apoptosis or signalling pathways; a noteworthy report by Davidson in 2019 shared the opinion that multitarget strategies must be adopted to reduce MIRI if appropriate because single approaches have a limited capacity to overcome complicated MIRI situations.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, numerous animal studies evaluating diverse protective mechanisms have confirmed the efficacy of cardioprotection in ameliorating MIRI. [1][2][3][4][5][6] The actual clinical application of some of these strategies, however, does not match the animal study applications, and it is difficult to predict the consequences in clinical practice from those seen in experimental research. [7][8][9] In this context, the unclear mechanism underlying the development of apoptotic pathways or involving key molecules in MIRI might significantly matter, especially for cell death and even associated signalling pathways during ischaemia-reperfusion, such as ERS-related apoptosis or signalling pathways; a noteworthy report by Davidson in 2019 shared the opinion that multitarget strategies must be adopted to reduce MIRI if appropriate because single approaches have a limited capacity to overcome complicated MIRI situations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression levels of certain mitochondrial proteins are altered following myocardial I/R injury and ischemic preconditioning (10)(11)(12). Recently, it was reported that D-Post may protect Langendorff I/R hearts via the mitochondrial ATP-sensitive potassium channel (mitoK ATP ) and the hypoxia-inducible factor-1/hypoxia response element pathway (13).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischemia-reperfusion injury (MIRI), which usually occurs in clinical settings, leads to severe outcomes for patients if no effective strategies are applied to inhibit the downstream apoptotic cascades. However, numerous animal studies that have revealed various protective mechanisms have also confirmed the efficacy of cardioprotection in overcoming MIRI (1)(2)(3)(4)(5)(6). However, the results achieved in the clinical application of these strategies have not been consistent with those achieved in experimental research (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%